2018
DOI: 10.1055/s-0038-1641587
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Delivery in Women with Higher Order Cesareans: A Cohort Study

Abstract: Compared with planned delivery at 39 weeks, a policy of planned delivery at 37 weeks was associated with a reduction in unscheduled deliveries, but there were no measured differences in perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…The association of URCD with untoward maternal outcome observed in our study was concordant with the findings of other studies, 8,9,[12][13][14]28 although some inves- tigations did not identify a similar association, despite detecting higher rates of URCD. [29][30][31] Interestingly, adverse maternal outcome encountered following URCD was not influenced by gestational age; performing URCD at early-term or at term was consistently associated with untoward maternal outcome, and was not improved by delivery at 39 WG.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The association of URCD with untoward maternal outcome observed in our study was concordant with the findings of other studies, 8,9,[12][13][14]28 although some inves- tigations did not identify a similar association, despite detecting higher rates of URCD. [29][30][31] Interestingly, adverse maternal outcome encountered following URCD was not influenced by gestational age; performing URCD at early-term or at term was consistently associated with untoward maternal outcome, and was not improved by delivery at 39 WG.…”
Section: Discussionsupporting
confidence: 92%
“…30 Another prominent observation from our study is that, besides labor, CD-order was an independent predictor of adverse maternal outcome, possibly through promoting the development of spontaneous labor before ERCD. 13,14,34 Composite adverse neonatal outcome was also more common in women who went into labor before ERCD, and this effect included delivery at 39 WG. Labor doubled the risk for adverse neonatal outcome, even after adjusting for possible confounding variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of perinatal mortality was similar between the two groups in the current study and did not increase significantly with increasing number of prior CDs which is consistent with previous studies [9][10][11]15].…”
Section: Discussionsupporting
confidence: 81%
“…A recent cohort study compared early term elective CD (at 37 weeks) to late term CD (at 39 weeks) reported higher rate of 5-minute Apgar score less than 7 at planned early CD (0.4 vs. 6.4%; p < 0.001) [15].…”
Section: Discussionmentioning
confidence: 99%